FeNi alloy supported on nitrogen-doped graphene catalysts by polyol process for oxygen reduction reaction (ORR) in proton exchange membrane fuel cell (PEMFC) cathode - Sirirak R. (2017)
© 2016, Springer Science+Business Media Dordrecht. A non-precious metal FeNi electrocatalyst (FeNi/NG) was prepared by a simple solution route called the polyol process for use as the oxygen reduction reaction (ORR) catalyst in polymer exchange membrane fuel cells. The nitrogen-doped graphene (NG) was synthesized from graphite oxide (GO) in a one-pot reactor via thermal annealing of GO-mixed melamine. The obtained NG presents high content of pyridinic-N and quaternary-N types with acceptable activity of ORR in acidic media by XPS and cyclic voltammetry techniques, respectively. The non-precious FeNi alloy nanoparticles (spherical-like nanoparticles mixed with hexagonal plate-like features) were successfully synthesized and well dispersed on the prepared NG by the polyol process confirmed by SEM-BSE and TEM analysis. The XRD and SAED results found FeNi and the carbon phase in the prepared catalysts. Finally, the CV technique shows that the peak potential of FeNi/NG is in the range of 0.12–0.34 V, which is close to that of the commercial Pt/C catalyst (0.35 V). To summarize, the obtained catalyst (FeNi/NG) revealed reliable electrocatalytic properties for ORR in a proton exchange membrane fuel cell cathode.